PROBLEMY LUDZI STARSZYCH NA WSI W ASPEKCIE PRAWNYM - Budzionwski, Roman (Wydział Prawa i Administracji UAM, 1999)
The paper aims to identify, from legal point of view, the main problems encountered by senior citizens in villages, and to answer the question whether the currently binding and enforceable regulations form adequate grounds on the basis of which a proper solution of those problems can be offered. The paper focuses on three main points: providing for the old age within a rural family, social insurance of farmers, and social welfare and health care of the village population. Problems encountered by that social group are particularly pronounced in context of the generation changes taking place in agriculture. Concluding, the Author claims that from legal point of view problems of the elderly living in villages have been gradually taken better care of, and the needs and expectations of senior citizens living in villages are more widely accepted and accommodated. This claim, however, does not mean that the situation of senior citizens in villages is satisfactory. Improvement in that respect may be achieved through better development of rural areas. An overall betterment of the Ufe in villages shall consequently improve the quality of life of senior citizens.
LEGAL ASPECTS OF PROBLEMS ENCOUNTERED BY SENIOR CITIZENS IN VILLAGES